2016
DOI: 10.1038/ncomms12114
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia causes transgenerational impairments in reproduction of fish

Abstract: Hypoxia is amongst the most widespread and pressing problems in aquatic environments. Here we demonstrate that fish (Oryzias melastigma) exposed to hypoxia show reproductive impairments (retarded gonad development, decrease in sperm count and sperm motility) in F1 and F2 generations despite these progenies (and their germ cells) having never been exposed to hypoxia. We further show that the observed transgenerational reproductive impairments are associated with a differential methylation pattern of specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 53 publications
4
113
0
Order By: Relevance
“…Indeed, stable transmission over multiple generations has been demonstrated by several studies (Agrawal et al 1999;Anway et al 2006;Rechavi et al 2011;Rechavi et al 2014), but such evidence remains scattered and inconsistent (Shama & Wegner 2014;Walsh et al 2014;Groot et al 2016). Moreover, although epigenetic changes are anticipated to underlie longterm transgenerational effects, there is little evidence for such causality, but see (Rechavi et al 2014;Wang et al 2016;Zhang et al 2016;Zheng et al 2017). It is hence critical to assess the general longevity of transgenerational effects, which is essential to assess the adaptive role of such effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, stable transmission over multiple generations has been demonstrated by several studies (Agrawal et al 1999;Anway et al 2006;Rechavi et al 2011;Rechavi et al 2014), but such evidence remains scattered and inconsistent (Shama & Wegner 2014;Walsh et al 2014;Groot et al 2016). Moreover, although epigenetic changes are anticipated to underlie longterm transgenerational effects, there is little evidence for such causality, but see (Rechavi et al 2014;Wang et al 2016;Zhang et al 2016;Zheng et al 2017). It is hence critical to assess the general longevity of transgenerational effects, which is essential to assess the adaptive role of such effects.…”
Section: Introductionmentioning
confidence: 99%
“…Waterborne BaP has been to shown modify the global and gene specific DNA methylation during zebrafish development (Fang et al, 2013). Recently Wang et al (2016) demonstrated another pathway in which hypoxia could trigger epigenetic changes in the methylome of sperm, and alter expression of genes and proteins, leading to a reduction in motility and quantity of sperm in the F0, F1, and F2 generations of marine medaka. It is possible that hypoxia could target the egg, sperm or both, resulting in changes we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Under laboratory conditions, prolonged, continuous hypoxia (1.7–2.0 mg O 2 L −1 , 10–15 wks) depressed reproduction in Altantic croaker ( Micropogonias undulatus ) (Thomas and Rahman, 2011; Thomas et al, 2006) and Gulf killifish ( Fundulus grandis ) (1.34 mg O 2 L −1 , 30 d) (Landry et al, 2007). And, recently, such impairments were shown to extend from F0 to F1 and F2 generations in marine medaka (1.4 mg O 2 L −1 , 3 mo) (Wang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . () demonstrated transgenerational reproductive impairments in medaka fish ( Oryzias melastigma ) caused by hypoxia exposure of the parental generation. Sexually mature fish (F0) were exposed to either normoxic (5.8 ± 0.4 mg O 2 L −1 ) or hypoxic conditions (1.4 ± 0.2 mg O 2 L −1 ) for 1 month.…”
Section: Epigenetics In Aquaculturementioning
confidence: 99%
“…It has been suggested that low dissolved oxygen levels may be associated with chronic stress, fish growth deficit and increased infection susceptibility (Burt et al 2012). Wang et al (2016) demonstrated transgenerational reproductive impairments in medaka fish (Oryzias melastigma) caused by hypoxia exposure of the parental generation. Sexually mature fish (F0) were exposed to either normoxic (5.8 AE 0.4 mg O 2 L À1 ) or hypoxic conditions (1.4 AE 0.2 mg O 2 L À1 ) for 1 month.…”
Section: Epigenetics In Aquaculturementioning
confidence: 99%